EVALUASI TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 STUDI KASUS: CV. BATARA JAYA TRANSPORTASI (YOJOL) - Raissa Amanda Putri; Aryo Pratama; Agung Setiawan Hasibuan; Andriyani Dwi Astuti (JISTech (Journal of Islamic Science and Technology), 2021)
Currently, information technology is an important part for companies to meet their needs and support the achievement of the company's strategic plans. Providing competitive advantages, increasing effectiveness, time and reducing expenses is the role of information technology that is very vital in today's business area, as well as CV Batara Jaya Transportasi, which has prioritized information technology in daily activities. By examining information technology governance using the COBIT 5 framework in a company, it can be seen whether the company has met the indicator requirements. In this study, an audit of the governance framework and maintenance was conducted at CV. Batara Jaya Transportasi (YoJol) to find out the ability indicators and the results have been obtained by using a questionnaire distributed to the company. In this study, it was found that CV. Batara Jaya Transportasi (YoJol) has achieved the results expected.